The Effect of Institutional Arrangements and Human Resources Development on Employee Performance in North Sumatra Provincial Suitable Assessment Institutions - Nuraida Pohan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Human resource development needs to be implemented to improve the performance of the apparatus in realizing service quality. Increasing the competence of human resources of government officials and institutional arrangements will have an impact on improving the performance of human resources which is an important part in improving the quality of services, which in turn will have a positive impact on regional development. This study aims to determine the effect of human resource development and institutional arrangement on employee performance at the North Sumatra Province Conformity Assessment Institute. This type of research was conducted with an explanatory approach. The variables used are institutional arrangement and human resource development and employee performance. The population of this study were civil servants in the province of North Sumatra as many as 191 people. The sample of this study was 191 people using the census method. The results of this study indicate that institutional arrangement has a direct positive and significant effect on employee performance and human resource development has a direct positive and significant effect on employee performance.